Implementasi Digital Payment Gateway Midtrans Pada Sistem Agribisnis Di Temanggung (SIADIT) - Ramadhan, Aditya Wahyu; Susanto, Ajib; Saraswati, Galuh Wilujeng (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The agribusiness system in Pagergunung Village has not been fully functioning properly. Based on the results of the survey that the author conducted, production was not optimal due to several factors including extreme weather changes, pest and disease attacks and low knowledge of the technology used and declining sales prices at harvest. In this era of the industrial revolution 4.0, all areas of life will involve the role of information and communication technology, one of which is in the field of agriculture. The application of technology in agriculture can be realized in the form of making a website for selling agricultural products so as to increase people's income through the creation of an agribusiness system, especially a marketing system through an e-marketplace that is connected to a paymet gateway. From the results of the blackbox test with a total of 25 respondents stated that online marketing media through the SIADIT e-marketplace application facilitates product promotion so as to increase farmers' income.